Geotechnical Improvement of Dredged Marine Soil using Blended Cement and Rice Husk Ash for Subgrade : Strength and Mix Evaluation - WAN HASRY, WAN AFFIRA ROHAIZA; SANI, SALINA (Progress in Engineering Application and Technology, 2026)
Dredged Marine Soil (DMS) is a waste material produced from dredging activities in marine waters. Although recent studies have shown its potential use in construction, untreated DMS is generally unsuitable for direct application, especially in road construction. Therefore, DMS must be mixed with stabilizers, such as cementitious or pozzolanic materials, to enhance its strength, durability, and load-bearing capacity prior to use in road construction The characteristics of DMS are high moisture content, low strength, and high compressibility. This study aims to evaluate the effectiveness of DMS stabilization using a mixture of Ordinary Portland Cement (OPC) and Rice Husk Ash (RHA) for use as a subgrade layer in road construction. To identify DMS characteristics and chemical composition of RHA, laboratory tests such as hydrometer, Atterberg limit, compaction characteristics, Unconfined Compressive Strength (UCS), California Bearing Ratio (CBR) and Scanning Electron Microscopy (SEM). The mixing ratio of cement (4%, 6%, and 8%) and RHA (5% and 10%) were tested at curing periods of 7, 14, and 28 days. The results showed that untreated DMS had low strength and did not meet the requirements of the JKR (2020) specification for subgrade applications. The addition of cement and RHA was proven to significantly improve the mechanical performance of DMS soil, where the strength increased in line with the curing period. The optimum mixture was identified at a ratio of 5% RHA and 6% cement, which met the minimum strength requirements of road subgrade with more efficient cement usage. SEM analysis confirmed the presence of amorphous silica and the formation of binding products in RHA contributed to the increase in soil strength. Overall, this study proved that the use of cement and RHA mixture is an effective and sustainable method to improve the engineering properties of marine dredged soil for road construction applications.